Prevalence of violence towards nursing staff in Slovenian nursing homes - Gabrovec, Branko (Zdr Varst, 2016)
INTRODUCTION: The purpose of this research was to identify the prevalence of violence towards nursing staff in Slovenian nursing homes. METHODS: For the purpose of this study, a non-experimental sampling method was employed, using a structured questionnaire as a data collection instrument (n=527). The contents of the questionnaire proved valid and reliable, with a high enough degree of internal consistency (Cronbach Alpha minimum 0.82). RESULTS: The nursing staffs working in nursing homes for senior citizens are at high risk of violence. In the last year, the employees were most often faced with verbal violence (71.7%), physical violence (63.8%) and sexual violence (35.5%). 35.5% of employees suffered injuries at their working place. During aggressive outbursts of nursing home residents, employees particularly experience vulnerability, fear and insecurity. CONCLUSION: There is a need for a comprehensive approach to tackle workplace violence. Some psychiatric health care facilities have already introduced certain measures in this field, and reduction of workplace violence proves that it is possible to reduce aggressive outbursts of patients. After conducting further quantitative research, which would expose detailed characteristics and the background of such violence, it would be sensible to develop similar measures in the field of health care in nursing homes.